A State Space Model for Spatial Updating of Remembered Visual Targets during Eye Movements - Mohsenzadeh, Yalda; Dash, Suryadeep; Crawford, J. Douglas (Frontiers in Systems Neuroscience, 2016)
In the oculomotor system‎, ‎spatial updating is the ability to aim a saccade toward a remembered visual target position despite intervening eye movements‎. ‎Although this has been the subject of extensive experimental investigation‎, ‎there is still no unifying theoretical framework to explain the neural mechanism for this phenomenon‎, ‎and how it influences visual signals in the brain‎. ‎Here‎, ‎we propose a unified state-space model (SSM) to account for the dynamics of spatial updating during two types of eye movement; saccades and smooth pursuit‎. ‎Our proposed model is a nonlinear SSM and implemented through a recurrent radial-basis-function neural network in a dual Extended Kalman filter (EKF) structure‎. ‎The model parameters and internal states (remembered target position) are estimated sequentially using the EKF method‎. ‎The proposed model replicates two fundamental experimental observations‎: ‎continuous gaze-centered updating of visual memory-related activity during smooth pursuit‎, ‎and predictive remapping of visual memory activity before and during saccades‎. ‎Moreover‎, ‎our model makes the new prediction that‎, ‎when uncertainty of input signals is incorporated in the model‎, ‎neural population activity and receptive fields expand just before and during saccades‎. ‎%This study suggests that visual remapping phenomena‎ -‎and thus subjective space constancy- ‎originates from the requirements of motor behavior‎. These results suggest that visual remapping and motor updating are part of a common visuomotor mechanism‎, ‎and that subjective perceptual constancy arises in part from training the visual system on motor tasks.